Pengaruh Pendidikan dan Pelatihan Terhadap Kinerja Guru Pada SMA Muhammadiyah Martapura - Audah, Zacky (Universitas Hang Tuah, 2020)
The purpose of this study was to determine and analyze the effect simultaneously and partially on education and training on teacher performance at SMA Muhammadiyah Martapura. This type of research is an associative study which explains the relationship and influence between education and training variables on their influence on teacher performance at SMA Muhammadiyah Martapura. The population was all teachers at SMA Muhammadiyah Martapura, amounting to 85 people. The sample taken in this study were 43 respondents. The validity of the questionnaire was tested by using the Pearson Product Moment correlation method, while the reliability test of the questionnaire used the Cronbach Alpha method. The data analysis technique was carried out using the Multiple Linear Regression method. Based on the research results and data analysis, it was concluded that; (1) simultaneously the education and training variables have an effect on teacher performance at SMA Muhammadiyah Martapura. (2) based on the partial t test, education and training have a significant effect on teacher performance at SMA Muhammadiyah Martapura. (3) the education variable has a dominant influence on teacher performance at SMA Muhammadiyah Martapura. The results of the determination test as obtained by the value of Adjusted R Square (R2) are 0.537 or equivalent to 53.7%. This means that the independent variable consisting of education (X1), training (X2) has an influence on the dependent variable, namely teacher performance (Y) of 53.7%. Meanwhile, the remaining 46.3% is influenced by other variables outside the model in this study.